1998
DOI: 10.1128/mmbr.62.4.1191-1243.1998
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cdc28 Cyclin-Dependent Protein Kinase Activity during the Cell Cycle of the Yeast Saccharomyces cerevisiae

Abstract: SUMMARY The cyclin-dependent protein kinase (CDK) encoded by CDC28 is the master regulator of cell division in the budding yeast Saccharomyces cerevisiae. By mechanisms that, for the most part, remain to be delineated, Cdc28 activity controls the timing of mitotic commitment, bud initiation, DNA replication, spindle formation, and chromosome separation. Environmental stimuli and progress through the cell cycle are monitored through checkpoint mechanisms that influence Cdc28 activity at key ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
213
0
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(221 citation statements)
references
References 688 publications
(1,382 reference statements)
1
213
0
7
Order By: Relevance
“…In yeast, Cdc28 kinase is the central coordinator of the major events of cell division cycle promoting the transition of cells from G1 to S phase, progression through S phase, and entry into mitosis. CKS1 function is controversial but it may play an important role at the G2/M checkpoint (Mendenhall and Hodge, 1998). Other roles for the CKS1/CDC28 complex may be to enhance RNA polymerase elongation (Yu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, Cdc28 kinase is the central coordinator of the major events of cell division cycle promoting the transition of cells from G1 to S phase, progression through S phase, and entry into mitosis. CKS1 function is controversial but it may play an important role at the G2/M checkpoint (Mendenhall and Hodge, 1998). Other roles for the CKS1/CDC28 complex may be to enhance RNA polymerase elongation (Yu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thus C. neoformans must have two critical commitment processes, one to DNA synthesis, and the other to budding. This independence between DNA synthesis and budding enables cells to continue to grow even after the cell population stops dividing, producing large unbudded G 2 cells in the stationary phase [4], in contrast to the smaller cells in S. cerevisiae [9]. Recently we reported that ploidy shift occurs frequently in C. neoformans [10].…”
Section: Discussionmentioning
confidence: 99%
“…We thus expressed the Sld2-P1 protein and the Dpb11-C protein composed of the C-terminal portion of Dpb11 fused to glutathione S transferase (GST) in Escherichia coli and purified them ( Supplementary Figure 2). When we phosphorylated Sld2-P1 with recombinant Cdc28-Clb5 (Mendenhall and Hodge, 1998) (rCdc28-Clb5), the yeast S-phase-specific CDK prepared from E. coli, Sld2-P1 migrated slower than the unphosphorylated form in (Bartel and Fields, 1995). The resultant plasmids and pACT2-DPB11 (Kamimura et al, 1998) were introduced into the yeast strain L40 and the interaction was detected by lacZ expression in colour.…”
Section: A Phosphorylated 28-amino-acid Stretch Of Sld2 Binds To Dpb11mentioning
confidence: 99%